The results of orthotopic heart transplantation using the bicaval technique - B. M. Todurov; H. I. Kovtun; O. A. Loskutov; S. R. Maruniak; D. O. Loskutov; A. Yu. Melnyk (Сучасні медичні технології)
Circulatory failure, which develops in the final stages of the course of the most heart diseases, is a link in the progressive process. This process is accompanied by a significant decrease in the quality of life, as well as high disability and mortality.